Analisis Kinerja Keuangan Pada Perusahaan Wijaya Karya Beton - Hasbi Ashshiddiqi; Bobi Sadli; Ratih Kusumastuti (Universitas 45 Surabaya, 2023)
The stock cost is straightforwardly corresponding to the company esteem, the lower the stock cost, the lower the company esteem and bad habit versa. The higher the stock cost. This article points to decide the impact of budgetary execution on firm esteem with profit approach as a directing variable. company execution includes a critical impact on firm esteem in fabricating companies on the Wijaya Karya Beton. Hence, companies have to be pay consideration to performance pointers that influence company esteem and endeavor to move forward company execution in arrange to get the next esteem.